The PROGRAM study: awake mapping versus asleep mapping versus no mapping for high-grade glioma resections : study protocol for an international multicenter prospective three-arm cohort study - Gerritsen, Jasper; Dirven, Clemens Maria Franciscus; De Vleeschouwer, Steven; Schucht, Philippe; Jungk, Christine; Krieg, Sandro; Nahed, Brian Vala; Berger, Mitchel Stuart; Broekman, Marike Lianne Daphne; Vincent, Arnaud Jean Pierre Edouard (BMJ open, 2021)
Introduction - The main surgical dilemma during glioma resections is the surgeon’s inability to accurately identify eloquent areas when the patient is under general anaesthesia without mapping techniques. Intraoperative stimulation mapping (ISM) techniques can be used to maximise extent of resection in eloquent areas yet simultaneously minimise the risk of postoperative neurological deficits. ISM has been widely implemented for low-grade glioma resections backed with ample scientific evidence, but this is not yet the case for high-grade glioma (HGG) resections. Therefore, ISM could thus be of important value in HGG surgery to improve both surgical and clinical outcomes. - Methods and analysis - This study is an international, multicenter, prospective three-arm cohort study of observational nature. Consecutive HGG patients will be operated with awake mapping, asleep mapping or no mapping with a 1:1:1 ratio. Primary endpoints are: (1) proportion of patients with National Institute of Health Stroke Scale deterioration at 6 weeks, 3 months and 6 months after surgery and (2) residual tumour volume of the contrast-enhancing and non-contrast-enhancing part as assessed by a neuroradiologist on postoperative contrast MRI scans. Secondary endpoints are: (1) overall survival and (2) progression-free survival at 12 months after surgery; (3) oncofunctional outcome and (4) frequency and severity of serious adverse events in each arm. Total duration of the study is 5 years. Patient inclusion is 4 years, follow-up is 1 year. - Ethics and dissemination - The study has been approved by the Medical Ethics Committee (METC Zuid-West Holland/Erasmus Medical Center; MEC-2020-0812). The results will be published in peer-reviewed academic journals and disseminated to patient organisations and media. - Trial registration number - ClinicalTrials.gov ID number - NCT04708171 - (PROGRAM-study), - NCT03861299 -(SAFE-trial)
Gesehen am 20.01.2022